Social perspectives on deforestation, land use change, and economic development in an expanding agricultural frontier in Northern Argentina - Huaranca, Laura Liliana; Iribarnegaray, Martín Alejandro; Albesa, Federico; Volante, Jose Norberto; Brannstrom, Christian; Seghezzo, Lucas (Elsevier, 2019)
The idea that agricultural production and environmental conservation are almost incompatible has divided nature protectionists, advocates for indigenous peoples, and agricultural producers. Discourses seem to cluster along strong, usually dichotomous alternatives such as “production versus conservation”. This apparently hegemonic “common sense” is generally promoted by enviromental non-governmental organizations and groups of large-scale agricultural producers, and it is constantly reproduced and exacerbated by the media, despite its negative consequences for social consensus and policy making. We present here results of a study in an expanding agricultural frontier in northern Argentina in which we identified and described social perspectives on deforestation, land use change, and economic development. Following an empirically based, quali-quantitative approach (Q methodology), we found that actual social perspectives did not conform to a simplistic production versus conservation dichotomy. Our case study suggests that some environmental governance processes may consolidate dichotomous debates that favor the interests of powerful groups of stakeholders. Knowledge on social perspectives could help understand complex social-environmental issues and help policy makers take decisions in the direction of more sustainable and inclusive land use practices.